(untitled) (New York, 2005)
Many of the Six Sigma methods successfully used in manufacturing are now being utilized in the transactional and service sectors. However, business-specific issues such as customer billing, order processing, and call center management require a modified set of problem-solving and analytical tools. This resource addresses those differences and provides a roadmap for impelementing "customer-centric" Six Sigma.
Keywords: Process control,Six sigma (Quality control standard)